2015
DOI: 10.1016/j.bbi.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-induced sepsis induces long-lasting affective changes in the mouse

Abstract: Post-septic encephalopathy is a poorly understood condition in survivors of sepsis that is characterised by cognitive and affective impairments. In this study we have sought to better understand this condition by undertaking a comprehensive behavioural and cognitive assessment of mice who had previously survived sepsis. Mice were treated with lipopolysaccharide (LPS; 5mg/kg) and one month after this assessed on a battery of tests. Post-septic animals were found to display significantly more immobility in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
97
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 80 publications
10
97
1
Order By: Relevance
“…Clinical studies for SE reported that patients with SE often suffered from hypotension [25], imbalance of amino acids in plasma [26], and neuronal injury with edema [27,28]. Several lines of evidences suggest that a rodent model of SE showed aberrant behavior: altered sensory function [29,30], increased anxiety [31,32], and cognitive impairment [33]. These results are similar to the symptoms of brain dysfunction in SE patients [34].…”
Section: Etiologysupporting
confidence: 74%
“…Clinical studies for SE reported that patients with SE often suffered from hypotension [25], imbalance of amino acids in plasma [26], and neuronal injury with edema [27,28]. Several lines of evidences suggest that a rodent model of SE showed aberrant behavior: altered sensory function [29,30], increased anxiety [31,32], and cognitive impairment [33]. These results are similar to the symptoms of brain dysfunction in SE patients [34].…”
Section: Etiologysupporting
confidence: 74%
“…Prolonged over-expression of pro-inflammatory cytokines has been extensively reported to cause neuronal loss [12,13,17,[26][27][28] . The present study makes a novel attempt to answer the questions concerning the long-term impact of early life bacterial infection on myelination and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…LPS derived from Escherichia Coli endotoxin (0111:B5, Sigma, CA, USA, 5 mg/kg) was dissolved in normal saline and injected intraperitoneally [13]. Control animals were injected with equivalent volumes (0.1 ml) of normal saline (vehicle).…”
Section: Experimental Protocolmentioning
confidence: 99%